An Analysis Of Students’ Grammar Mastery In Speaking At The First Grade Senior High School In Al Jauhar Islamic Boarding School - Aisyah, Siti (Jolly Journal of English Education, 2023)
This study was a quantitative approach with descriptive design. It aims to know the students’ grammar mastery in speaking. The researcher used a descriptive analysis technique with the percentage from the three point of measuring grammar mastery and the frequency from all sample. While the subject was the students of first grade senior high school at Al Jauhar. The research used cluster random sampling. There were 19 samples from 79 population.To collect data, this research used speaking test to find out students’ grammar mastery in speaking. Based on data analysis, the researcher has found the students’ grammar mastery was D with less category based on report value or KKM, which the dominant scale of grammatical meaning was scale 2 with percentage 63,2%, the dominant scale of grammatical meaning was scale 2 with percentage 57,9%, and the dominant scale of word in particular context was scale 3 with percentage 36,8%. The total score of students’ grammar mastery was 901 with average 47,4.